Energy Drinks as the Legal Cocaine? A Comparative Review of Cardiac Physiopathological and Histopathological Patterns - Alessandro Ghamlouch; Nicola Di Fazio; Maura Racciatti; Fabio Del Duca; Biancamaria Treves; Gaia De Angelis; Alessandra De Matteis; Aniello Maiese; Paola Frati (Cardiovascular Toxicology, 2025)
Energy drinks (EDs), widely consumed for their stimulant effects, typically contain caffeine alongside taurine, guarana, and other bioactive compounds. While generally regarded as safe, growing evidence links chronic EDs consumption to significant cardiovascular risks. Caffeine, the primary active ingredient, acts through adenosine receptor antagonism and increased calcium release, potentially provoking arrhythmias and myocardial stress. Taurine and other additives further influence cardiac excitability and contractility. This systematic review, conducted under PRISMA 2020 guidelines, investigated the cardiac histopathological consequences of chronic EDs use. A literature search spanning 2021 to March 2025 across PubMed, Google Scholar, and Scopus identified studies reporting EDs-related cardiac effects. Data extraction and analysis revealed consistent associations with QTc prolongation, atrial and ventricular arrhythmias, myocardial infarction, Takotsubo cardiomyopathy, and hypertensive episodes—even in young, healthy individuals. Animal studies support these findings, showing myocardial necrosis, myofiber disarray, mitochondrial damage, and inflammation, particularly when EDs are combined with alcohol. Notably, similarities between EDs and cocaine emerged, including shared mechanisms involving ion channel blockade, sympathetic overactivation, vasoconstriction, and prothrombotic states. Chronic use of either substance can result in structural heart damage and remodelling. Although EDs and cocaine differ in legal status and potency, their overlapping cardiovascular effects warrant greater clinical awareness and public education. Excessive EDs consumption poses a real cardiotoxic risk, especially in vulnerable populations, underscoring the need for further human research and potential regulatory consideration. Graphical Abstract

Corrigendum to “Effect of IL8 haplotype on immunological traits in periparturient dairy cows” [Vet. Immunol. Immunopathol. 238 (2021) 1–8/110288] - Giovanna De Matteis; Maria Carmela Scatà; Francesco Grandoni; Alessandra Crisà; Megan B. O’Brien; Kieran G. Meade; Gennaro Catillo (Veterinary Immunology and Immunopathology, 2023)

Evaluating the impact of improved maize varieties on food security in Rural Tanzania: Evidence from a continuous treatment approach - Menale Kassie; Moti Jaleta; Alessandra Mattei (Food Security, 2014)

Seasonal variation, weather and behavior in day-care children: a multilevel approach - Enrica Ciucci; Pamela Calussi; Ersilia Menesini; Alessandra Mattei; Martina Petralli; Simone Orlandini (International Journal of Biometeorology, 2013)

Polymorph Formation and Nucleation Mechanism of Tolfenamic Acid in Solution: An Investigation of Pre-nucleation Solute Association - Alessandra Mattei; Tonglei Li (Pharmaceutical Research, 2012)

Weather daily variation in winter and its effect on behavior and affective states in day-care children - Enrica Ciucci; Pamela Calussi; Ersilia Menesini; Alessandra Mattei; Martina Petralli; Simone Orlandini (International Journal of Biometeorology, 2011)

Solid-State Properties of the Cyclooxygenase-1-Selective Inhibitor, SC-560 - Sihui Long; Kathryn L. Theiss; Alessandra Mattei; Charles D. Loftin; Tonglei Li (AAPS PharmSciTech, 2010)